A Phenomenological approach to media art environments: The Immersive art experience and the Finnish art scene - Scacco, Lorella (fi=Turun yliopisto|en=University of Turku|, 2023)
This research focuses on immersive art, defined as a multimedia experience where visitors interact with artwork whilst immersed in a range of sensory experiences. In this dissertation, I investigate the immersive art experience from the perspective of art history, social theory, and media studies situated within a phenomenological theoretical framework. I present a comparative analysis of forms of immersive spatiality, including projected moving-image art, spatial environments, participatory installations, video art installations and interactive environments in the international art scene. One of my objectives is to emphasise the role of video art in the development of interactive and immersive art environments. The growing importance of spectators for giving meaning to the artwork allows immersivity to be analysed in relation to the notions of spectacle and spectatorship. I connect disciplines, practices and concepts by adopting principles from Maurice Merleau-Ponty’s phenomenological writings. Spatiality and motility are pivotal points in immersive experiences. Immersive art, as an embodied mutual experience, materialises the phenomenological concepts of spectatorship, corporeality, motility, porosity, chiasm, and encounter. I have selected a group of relevant Finnish artists from different generations to characterise the development of media art and, particularly, immersive media art in an international context. The group includes Eija-Liisa Ahtila, Lauri Astala, Laura Beloff, Hanna Haaslahti, Tuomas A. Laitinen, Erkka Nissinen, and Marjatta Oja. I examine the historical dissemination of phenomenology in Finland and a renewed interest in the 1990s which coincided with the spatialisation of video art and the emergence of immersivity. I also investigate the opening of Kiasma Museum of Contemporary Art and its impact on Finnish culture, and the recent Amos Rex Museum, specifically built for immersive exhibitions. Regarding the unstable nature of media art, I analyse the changes in displaying art collections and exhibitions, the new commitments of art museums and the innovative directions taken by media conservators. My examination of immersive art, with its performativity and transience, reveals environmentally friendly and sustainable aspects.

Fenomenologinen tulokulma mediataideympäristöihin. Immersiivinen taidekokemus ja Suomen taidekenttä Tämä tutkimus käsittelee immersiivistä taidetta multimediaalisena kokemuksena. Immersiossa kävijät ovat erilaisten aistimellisten kokemusten ympäröiminä vuorovaikutuksessa taiteen kanssa. Tutkin väitöskirjassani immersiivistä taidekokemusta fenomenologisessa teoriakehyksessä taidehistorian, yhteiskuntateorian ja mediatutkimuksen näkökulmasta. Esitän vertailevan analyysin immersiivisistä tilallisuuden muodoista, joihin sisällytän liikkuvan kuvan projisoinnit, tilateokset, osallistavat installaatiot, videoinstallaatiot ja interaktiiviset ympäristöt kansainvälisen taidekentän ilmiöinä. Yhtenä pyrkimyksenäni on painottaa videotaiteen merkitystä interaktiivisen ja immersiivisen taiteen kehityksessä. Katsojien kasvava rooli taideteoksen merkityksen muodostuksessa tarjoaa perustan immersion analyysille nimenomaan spektaakkelin ja katsojuuden viitekehyksessä. Yhdistän eri tieteenaloja, käytäntöjä ja käsitteitä toisiinsa Maurice Merleau-Pontyn fenomenologisten kirjoitusten avulla. Tilallisuus ja liike ovat immersiivisten kokemusten ytimessä. Jaettuna ruumiillisena kokemuksena immersiivinen taide ilmentää materiaalisesti fenomenologisia katsojuuden, ruumiillisuuden, liikkeessä olemisen, huokoisuuden, kiasman ja kohtaamisen käsitteitä. Olen valinnut joukon eri sukupolvia edustavia suomalaistaiteilijoita hahmot-taakseni mediataiteen ja erityisesti immersiivisen mediataiteen kansainvälisiä kehityskulkuja. Heihin lukeutuvat Eija-Liisa Ahtila, Lauri Astala, Laura Beloff, Hanna Haaslahti, Tuomas A. Laitinen, Erkka Nissinen ja Marjatta Oja. Käsittelen fenomenologian saapumista Suomeen sekä siihen 1990-luvulla videotaiteen tilallistumisen ja immersion esiin nousun yhteydessä uudelleen virinnyttä mielenkiintoa. Tarkastelen myös Nykytaiteen museo Kiasman perustamista ja sen vaikutusta suomalaiseen kulttuuriin, samoin kuin vastikään avattua Amos Rex -taidemuseota, joka on rakennettu erityisesti immersiivisiä näyttelyitä silmällä pitäen. Analysoin muutoksia taidekokoelmien ja näyttelyiden esillepanossa, taidemuseoiden uudenlaisia sitoumuksia ja mediataiteen kuratoinnin uutta luovia suuntia suhteessa mediataiteen nopeasti muuttuvaan luonteeseen. Painottamalla performatiivisuutta ja hetkellisyyttä nostan immersiivisen taiteen analyysissani näkyville sen ympäristöystävällisiä ja kestäviä ulottuvuuksia.